Influencing Factors in the Depth-Usage of Social Media as the Business Platform by Student Entrepreneurs - Hafiz Rahman; Rahmad Hidayat (AMAR (Andalas Management Review), 2019)
This paper examines factors that influence the depth-usage of social media as a business platform among student entrepreneurs by focusing analysis on the mediating effect of social media adoption. The study uses The Unified Theory of Acceptance and Use of Technology (UTAUT) Model which identifies factors that can influence individuals’ behavioral patterns to accept and to use technology as the main theoretical/conceptual foundation.The study is a quantitative study which operates relational analysis between variables. A survey through the questionnaire with 142 student entrepreneurs in three state owned universities in Padang, Indonesia was undertaken to collect primary data and information. The result was further analyzed by using Structural Equation Modelling (SEM) Partial Least Square (PLS) and causal step analysis in order to investigate the relationship between each variable and the mediating effect of social media adoption on factors that influence the depth-usage of social media as the business platform used by students entrepreneurs. The study found that performance expectation, perceived trust and social influence as the major factors that influence the adoption of social media usage as the business platform by student entrepreneurs. Meanwhile, perceived risks does not bring positive and significant influence. However, the mediating effect of the adoption of social media usage is only found in the performance expectancy when it influences the depth-usage of social media as the business platform by the student entrepreneurs.